PENGENDALIAN PIUTANG TERHADAP TINGKAT KEBUTUHAN MODAL KERJA SERTA DAMPAKNYA TERHADAP TINGKAT PROFITABILITAS - Utami, Setyaningsih Sri (Universitas Slamet Riyadi, 2011)
ABSTRACT One of the company's strategy to increase of sales volume is to Provide the receivables, the receivables are more and more hope of profit but Also the Greater the risk the company is Also getting bigger and of course investment or working capital to be provided by companies are Also increasingly working a lot. Capital apart closely related to the operation of company daily as well as indicate the level of safety or margin of safety of creditors, especially the short term. The existence of efficient working capital allows the company to operate as efficiently as possible and the company Had no trouble or face the Dangers That cans be the caused by the financial crisis. Keywords: volume of sales, receivables, working capital, margin of safety